Meaning making, self‐determination theory, and the question of wisdom in personality. Issue 1 (25th April 2018) - Bauer, Jack J.; King, Laura A.; Steger, Michael F.
Abstract: Self‐determination theory (SDT) has advanced the most comprehensive model of motives for human flourishing in the field of personality psychology and beyond. In this article, we evaluate SDT relative to the process of meaning making, particularly from a narrative perspective, showing what SDT can and cannot explain about the construction of self‐identity and its relation to human flourishing. On the one hand, SDT explains how subjective assessments of need fulfillment drive the process of self‐determined living. The internal motives that follow such fulfillment serve as important themes in people's life stories that predict several markers of hedonic and eudaimonic well‐being. On the other hand, SDT's focus on subjective fulfillment limits what SDT can explain about how wisdom, which is a canonical good of both eudaimonia and meaning making, helps people make sense of life's more difficult or unfulfilling events. SDT may facilitate a facet of wisdom that is more subjective and experiential but not the critical facet of wisdom defined by objectively more complex structures of interpretation.